Chalmers v Chalmers*. (29th April 2020) - Stoljar, Daniel
Abstract: This paper brings out an inconsistency between David Chalmers's dualism, which is the main element of his philosophy of mind, and his structuralism, which is the main element of his epistemology. The point is ad hominem, but the inconsistency if it can be established is of considerable independent interest. For the best response to the inconsistency, I argue, is to adopt what Chalmers calls 'type‐C Materialism', a version of materialism that has been much discussed in recent times because of its promise to move us beyond the stand‐off between standard versions of materialism and dualism. In turn, if that version of materialism is true, both dualism and structuralism should be rejected.